Gender Needs Assessment in Conflict-Affected Areas in Thailand's Southernmost Provinces - World Bank (World Bank, Washington, DC, 2012)
The objectives of the gender needs assessment study is to add value to and complement the Post Conflict Fund (PCF) supported conflict; and to add to the body of knowledge regarding women, men and their families affected by the conflict as well as the government's policies in addressing this conflict. The century-long struggle in Thailand's southernmost provinces of Yala, Narathiwas and Pattani broke into open violence in January 2004, and has since escalated, involving over 9,000 individuals in violence, widowing nearly 1,000 women and orphaning over 1,200 children. The conflict historically centered on the relationship between Malayu-speaking Muslims majority in the three provinces, and the largely Buddhist nation. The aim of the gender needs assessment is to deepen the understanding of the conflict situation experienced by men and women in the southern conflict areas; and to help identify appropriate interventions aimed at improving the lives of men and women in conflict situations. This study had been undertaken with the explicit purpose of developing a gendered understanding of dimensions of the conflict and the existing or possible sources of peace and resilience to conflict.